Impact of a large-scale coach education program from a lifelong-learning perspective - Deek, D.; Werthner, P.; Paquette, K. J.; Culver, D. M. (Journal of Coaching Education, 2013)
This study examines the impact of a coach education program on coach learning and perceived changes to coaching practices, while situating this episodic learning experience within a lifelonglearning perspective. Three sets of in-depth interviews were conducted with 10 coaches taking part in one of three competition-development modules within Canada`s National Coaching Certification Program (Coaching and Leading Effectively, Managing Conflict, and Psychology of Performance). It was found that (a) the coaches` biographies varied widely, (b) all of the coaches reported learning from the modules, (c) eight of ten coaches reported a change in their coaching practices as a result of participation in one of the modules, and (d) the coaches credited a combination of mediated, unmediated, and internal learning situations for their learning before and after the modules. These findings suggest that a large-scale coach education program can have an impact on coaches when the program takes a lifelong-learning perspective and integrates constructivist principles into its design and delivery.